2021
DOI: 10.3390/app11135888
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Modern Artificial Lighting on the Optimum Window-to-Wall Ratio of Residential Buildings in Jordan

Abstract: Energy savings gained through natural lighting could be offset by the loss of energy through windows; therefore, the target of this study is to examine the effects of enhancing the efficiency of lighting systems on the optimum window-to-wall ratio (WWR) of Jordanian residential structures. This research proposes the hypothesis that the WWR of residential structures that contain artificial lighting systems with increased efficiency will be lower than buildings in which solar lighting is provided. The energy sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Window-to-Wall Ratio (%) = 0.836 × (LED Lighting lamps efficiency (lm/W)) −0.27 It is therefore proposed that in general, the WWR for residential structures equipped with LED lighting systems can be reduced to 17%, which is less than the WWR threshold of 40% recommended in the ASHRAE standard, as well as other building codes [40,47]. Additionally, it is recommended that energy simulation software should be employed when designing future residential buildings in order to optimize the WWR, because changes made to one element have the potential to impact various other interconnected elements.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Window-to-Wall Ratio (%) = 0.836 × (LED Lighting lamps efficiency (lm/W)) −0.27 It is therefore proposed that in general, the WWR for residential structures equipped with LED lighting systems can be reduced to 17%, which is less than the WWR threshold of 40% recommended in the ASHRAE standard, as well as other building codes [40,47]. Additionally, it is recommended that energy simulation software should be employed when designing future residential buildings in order to optimize the WWR, because changes made to one element have the potential to impact various other interconnected elements.…”
Section: Resultsmentioning
confidence: 99%
“…The material used for the window frame was aluminum and its total U W/m 2 .K. The glazing of the outside windows was comprised of Generic blu ness of 6 cm, followed by an air gap of 5 cm, and finally, a Generic clear glaz a thickness of 6 cm, which has a total U-value of 3.1 W/m 2 .K, overall sola (SHGC) of 0.7, direct solar transmission of 0.6, and light transmission of 0.7 the windows was modified according to 11 distinct scenarios, with a favo 1.5 m [40].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Albatayneh et al, offered useful guidance regarding the optimum Window-Wall-Ratio (WWR) for key decision-makers when designing energy-efficient buildings in Jordan. The findings indicated that the typical WWR in Jordan that have efficient LEDs lighting installed could be lower than the highest WWR stipulated by the American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE) standards [20]. Instead of the classical approach based on static metrics-i.e., Daylight Factor, dynamic metrics provide a more accurate quantification of energy savings in electric lighting when compared to traditional daylight static concepts.…”
Section: Figure 3 How Can Bim Model Contributes To Lighting Design An...mentioning
confidence: 97%
“…Occupant behaviour and adaptation to the current environment can save a significant amount of cooling energy through the application of shading devices, the use of night ventilation, and the employment of adaptation techniques (wearing breathable clothes, drinking water, and using low-energy solutions, such as fans) instead of completely relying on mechanical systems. The amount of possible savings can exceed 50% of the cooling energy depending on the adaptation level and the awareness of the occupants [41][42][43].…”
Section: Energy Saving Through Solar Shading and Occupant's Behaviourmentioning
confidence: 99%